An Alternative Macrophage Activation Pathway Regulator, CHIT1, May Provide a Serum and Synovial Fluid Biomarker of Periprosthetic Osteolysis. Issue 2 (July 2018) - Trehan, Samir K.; Zambrana, Lester; Jo, Jonathan E.; Purdue, Ed; Karamitros, Athanos; Nguyen, Joseph T.; Lane, Joseph M.
Background: Periprosthetic osteolysis (PPO) is a frequent indication for total hip replacement (THR) failure. Currently, PPO diagnosis occurs in advanced stages that often necessitate complex revisions due to bone loss. PPO biomarkers could facilitate earlier diagnosis. Alternative macrophage activation pathway regulators, chitotriosidase (CHIT1) and CC chemokine ligand 18 (CCL18), have increased periprosthetic expression in patients undergoing revision THR for osteolysis. We hypothesized that synovial fluid and serum levels of CHIT1 and CCL18 would be increased in patients undergoing revision THR for PPO versus controls without osteolysis. Methods: In this prospective case-control study, 60 patients undergoing revision metal-on-polyethylene THR at Hospital for Special Surgery were screened preoperatively from January 2013 to December 2014. Twenty "osteolysis" patients who underwent revision for PPO (based on imaging and operative reports) and 10 "control" patients (with stable implants) who underwent revision for recurrent dislocation or a mechanical etiology were included. Among osteolysis and control patients, 11/20 and 4/10 were male; average age was 68 and 63 years, respectively; 9/20 and 3/10 had cemented femoral components; and average implant longevity was 15 and 5 years, respectively. Preoperative serum and intraoperative synovial fluid samples were collected. CHIT1 and CCL18 were quantified via enzyme-linked immunosorbent assay. Significance was assessed via nonparametric Mann-Whiney U test. Results: CHIT1 was significantly increased in both synovial fluid (3727 versus 731 nanomoles [nM]) and serum (98 versus 39 nM) in the osteolysis versus control patients. CCL18 levels were also significantly increased in osteolysis versus control patients' synovial fluid (425 versus 180 nM) but not their serum. Conclusions: In this prospective case-control study, CHIT1 was identified as a novel synovial fluid and serum biomarker of PPO. CHIT1 expression is induced during macrophage activation in response to wear debris. CHIT1 monitoring may facilitate early diagnosis of THR PPO. Furthermore, CHIT1 may represent a novel therapeutic target for PPO.